Is cholecystectomy a reasonable treatment option for simple gallbladder polyps larger than 10 mm? - Park, Hye Yon (World J Gastroenterol, 2015)
AIM: To determine the relevance of the 10-mm size criterion of the generally accepted surgical indication for gallbladder polyps (GBPs). METHODS: We collected data of patients who were confirmed to have GBPs through cholecystectomy at Samsung Medical Center between January 1997 and December 2012. Among the patients who underwent cholecystectomy for GBP, those with a definite evidence for malignancy such as adjacent organ invasion, metastasis on preoperative imaging studies, polyp larger than 20 mm, absence of preoperative imaging study results, and patients having gallstones were excluded. We retrospectively collected and analyzed information on patient’s clinical characteristics, symptoms, ultrasonographic findings, and blood laboratory tests. RESULTS: A total of 836 patients who had undergone cholecystectomy were retrospectively analyzed. Seven hundred eighty patients (93%) had benign polyps, whereas 56 patients (7%) had malignant polyps. Of the 56 patients with malignancy, 4 patients (7%) had borderline GBP (10-12 mm) and a patient had small GBP (< 10 mm) with T2 stage. We conducted an ROC curve analysis to verify the 10-mm size criteria (AUC = 0.887, SD = 0.21, P < 0.001). In the ROC curve for polyp size and malignancy, sensitivity and specificity of the 10-mm size criterion was 98.2% and 19.6%, respectively. The specificity of the 11-mm and 12-mm size criteria was 44.6% and 56%, respectively, whereas the sensitivity of these two size criteria was similar. We defined the GBPs of 10 to 12 mm as a borderline-sized GBP, which were found in 411 patients (49%). In this group, there was a significant difference in age between patients with benign and malignant GBPs (47 years vs 60 years, P < 0.05). CONCLUSION: GBPs larger than 13 mm need immediate excision whereas for borderline-sized GBPs detected in young patients, careful medical observation can be a rational decision.